Melhorando a segurança do paciente em uma organização de saúde brasileira utilizando o pensamento enxuto - Da Silva, Macáliston G.; Paz, Michele da Rosa; Silva, Rafael Maciel da; Carvalho, Maurício Nunes Macedo de; Bianchini, Victor; Lara, Rodrigo; Pergher, Isaac (Brazilian Journal of Production Engineering, 2025)
This paper aims to present the trajectory of a Brazilian healthcare organization in a Lean Healthcare (LH) project to enhance patient safety and integrate a culture of continuous improvement. The action research is about a unit dedicated to diagnostic imaging medicine to investigate and improve patient safety. Advances in mitigating inappropriate processing, patient waiting, and wastes due to movements of employees during the on-site exams were evident. The proposed changes directly impacted on reducing the risk of patient safety failures, enhanced patient identification, and makespan reduction by 30.37%. The article can motivate researchers and health managers to explore in depth the LH as a foundation for management decisions, especially in emerging countries. The paper illustrates that LH provides a practical framework for healthcare organizations to enhance patient safety, improve operational efficiency, and reduce waste through systematic process improvements and a culture of continuous learning. This research contributes by providing a real-world case of LH implementation in a challenging environment, detailing specific waste categories and mitigation strategies, and reinforcing the value of Lean principles for enhancing patient safety and operational efficiency in healthcare.